Quantitative trait loci impacting grain β‐glucan content in wild barley (Hordeum vulgare ssp. spontaneum) reveals genes associated with cell wall modification and carbohydrate metabolism. Issue 3 (10th May 2022) - Walling, Jason G.; Sallam, Ahmad H.; Steffenson, Brian J.; Henson, Cynthia; Vinje, Marcus A.; Mahalingam, Ramamurthy
Abstract: Barley ( Hordeum vulgare L.) seeds are a rich source of β‐glucans that can help reduce blood serum cholesterol content in human diets. However, high levels of this polysaccharide in the seeds causes inefficiencies such as slow lautering during the brewing process due to the higher wort viscosity. Thus, depending on the end use, barley breeding programs have opposing goals with respect to β‐glucan. Discovery of new alleles for β‐glucan content in exotic barley germplasm could have significant commercial importance. We leveraged the Wild Barley Diversity Collection (WBDC; N = 314), grown at University of California‐Davis experiment station, to characterize both the variation in β‐glucan content found in this wild barley subspecies ( Hordeum vulgare spp . spontaneum ) and to reveal chromosomal regions associated with this trait. Grain β‐glucan content ranged from 2.56 to 11.73% in the WBDC. Within structured subpopulations, geographical coordinates as well as annual precipitation data of original collection sites showed associations with differing levels of β‐glucan content. Genome‐wide association study identified a total of 13 quantitative traits loci (QTL) spread across the seven barley chromosomes that explained most of the variation in β‐glucan content in the WBDC. Previously reported genes associated with β‐glucan content such as β‐glucan synthases and hydrolases (e.g., callose synthase) were identified within these QTL regions. Genes such as Patatin and Nudix hydrolase provide novel targets for manipulating grain β‐glucan in barley. RNA‐seq data from both developing and germinating barley seeds for the annotated genes in the QTL regions provide further corroboration for a functional role for these genes in modulating seed β‐glucan levels. Core Ideas: Wild barley species exhibit extensive variation in seed beta glucan content. Environmental conditions in regions where accessions evolved may affect beta glucan levels. Genes involved in carbohydrate metabolism were in the identified QTL regions.